PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS PESERTA DIDIK KELAS X.7 SMA NEGERI 4 PEKANBARU - Angelina Agatha Hutabalian; Rini Dian Anggraini; Maimunah; Fadhli Alfathra (Jurnal Ilmiah Matematika Realistik, 2026)
Difficulties in connecting mathematical concepts with other concepts and real-life situations indicate that students’ mathematical connection ability is still relatively low. One effort to overcome this problem is the implementation of the Problem Based Learning (PBL) model, which emphasizes learning through contextual problems. This study aimed to improve the learning process and enhance the mathematical connection ability of Grade X.7 students at SMA Negeri 4 Pekanbaru on the topic of Systems of Linear Inequalities in Two Variables during the first semester of the 2025/2026 academic year. This study employed Classroom Action Research conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The participants were 43 students. The research instruments included lesson plans, observation sheets of teacher and student activities, and a mathematical connection ability test. Data were analyzed using descriptive qualitative and quantitative techniques based on three indicators: connections among mathematical concepts, connections between mathematics and other disciplines, and connections between mathematics and everyday life. The results showed that the implementation of the PBL model improved both the learning process and students’ mathematical connection ability. This was indicated by an increase in the number of students in the very high category from 8 students in Cycle I to 15 students in Cycle II, accompanied by a decrease in the number of students in the low category. The novelty of this study lies in examining the improvement of mathematical connection ability through the gradual implementation of PBL in each action cycle.